2018
DOI: 10.1177/1938640018783496
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Following Fasciotomy for Chronic Exertional Compartment Syndrome

Abstract: Level IV: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The overall patient satisfaction rate in the current series (78.1%) falls within the range described in other recent studies, such 84% by Campano et al, 6 76% by Micheli et al, 16 76% by Pasic et al, 18 and 60% by Slimmon et al 26 The mean percentage pain relief of 77.5% in the current series is similar to the 68% rate reported by Howard et al 11 Abramowitz and Schepsis 1 have suggested that fasciotomies in the deep posterior compartment may not relieve pain, and this is supported by additional studies that have found better pain improvement after release of the anterior/lateral compartments compared with the deep posterior compartment. 11,21,22,24 Regarding surgical technique, Maher et al 14 noted that patients achieve greater postoperative satisfaction and higher rates of return to sport (91% vs 66%) when all 4 compartments are released versus individual compartments. Beck et al 3 similarly noted that pediatric patients with isolated compartment release had higher rates of failure and reoperation than those with 4-compartment releases.…”
Section: Discussionmentioning
confidence: 99%
“…The overall patient satisfaction rate in the current series (78.1%) falls within the range described in other recent studies, such 84% by Campano et al, 6 76% by Micheli et al, 16 76% by Pasic et al, 18 and 60% by Slimmon et al 26 The mean percentage pain relief of 77.5% in the current series is similar to the 68% rate reported by Howard et al 11 Abramowitz and Schepsis 1 have suggested that fasciotomies in the deep posterior compartment may not relieve pain, and this is supported by additional studies that have found better pain improvement after release of the anterior/lateral compartments compared with the deep posterior compartment. 11,21,22,24 Regarding surgical technique, Maher et al 14 noted that patients achieve greater postoperative satisfaction and higher rates of return to sport (91% vs 66%) when all 4 compartments are released versus individual compartments. Beck et al 3 similarly noted that pediatric patients with isolated compartment release had higher rates of failure and reoperation than those with 4-compartment releases.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the seven studies (29)(30)(31)(32)(33)(34)(35) are presented in table 1. A total of 194 patients (100 male, 94 female) with a mean age of 24 years (range 15-55) were analyzed.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…A total of 194 patients (100 male, 94 female) with a mean age of 24 years (range 15-55) were analyzed. Six studies (29)(30)(31)(32)(33)(34) were retrospective cohort studies while one study (35) was a prospective cohort study. In six articles (29)(30)(31)(32)(33)35) study groups were allocated according to a two (2-CF) or four (4-CF) compartment release.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations